Direitos da sociedade em rede: a urgência de se falar num processo civil coletivo jurisdicional democrático - Rodrigues, Alexsandra Gato (2015)
This paper studies the need to overcome the procedural individualism embodied in a process model that is criticized. The research develops recognizing that the paradigms that have informed the industrial society are no longer sufficient to resolve the conflicts in society in recent decades. The process of classical institutes have long been powerless to show the protection of rights, especially the new collective rights. This bias is questioned whether the current process model is able to answer the collective demands. For development of this research will be used deductive approach method, as part of general issues such as the analysis of the evolution of civil procedure in the modern state, the individualistic procedural model to the collective civil procedure of the network society, then treat specific issues of civil procedure (collective) democratic judicial through the role of the Constitution. From the constitutionalization process is not seen in its formal aspect as a simple succession of acts essential to the jurisdictional function to incorporate an element of justice which makes it means by which promotes the achievement of values and constitutional principles. The collective process is perceived as a developer institute the democratic game, a "new" process model obtained by means of a "new" reading of the Constitution, it is possible from the recognition of the adversarial principle as the possibility of parties to influence the formation of critical and constructive manner, the content of judicial decisions (injunction Judgment of Origin), by means of a preliminary discussion of all participants.